The biology teacher’s professional knowledge on the teaching of evolution - Guerrero, Roger Steve; Fonseca-Amaya, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The research is based on the proposal of Fonseca and Martínez (2020), in which the construction of the biology teacher’s professional knowledge is presented as the integration/ transformation of five types of knowledge: disciplinary, didactic, of life history, of experience, and of context. The methodology is based on the analysis and interpretation of a case study of a practicing teacher at a declarative level. As a result of the research, it is evident that,since the teacher integrated and transformed her knowledge, three new and unique types of knowledge emerged: teaching evolution as a vehicle in the appropriation of a responsible human attitude towards the conservation of species; teaching and understanding biological evolution as a mechanism for mitigating attitudes associated with male chauvinism, xenophobia, and sexual discrimination; and teaching evolution and decision-making in theconstruction of critical citizenship.